Environmental Provisions in Trade Agreements: Effects on Andean and Southern Common Market Members - Paredes Quintana, Paula Noelia; Fairlie Reinoso, Alan; Martínez-Zarzoso, Inmaculada; Paredes Zegarra, Tania (Latin American Journal of Trade Policy, 2023)
This article investigates the impact of environmental clauses in regional trade agreements on the international trade of CAN and MERCOSUR countries between 2001 and 2019. We use a gravity model estimated with the PPML estimator to analyze the relationship between environmental provisions in trade agreements and total exports. We find that the simple inclusion of environmental provisions does not have a significant effect on trade. However, the presence of a Preferential Trade Agreement (PTA) in the midst of compliance is associated with a negative and significant effect on total exports. This result is accentuated if the trade occurs in a South-North structure. This finding complements previous research and provides a more complete understanding of the impact of environmental clauses on international trade in the countries of the region.